Theoretical Study on the Physiological and Hematological Effects of Basil (Ocimum Basilicum) Extract on Rats Exposed to a High-Fat Diet - Hannoonee, Iman Suri (American Journal of Botany and Bioengineering, 2025)
This theoretical research explores the potential physiological and hematological impacts of basil (Ocimum basilicum) extract on rats subjected to a high-fat diet (HFD). Given the alarming rise in obesity and metabolic diseases across the globe, there is a growing demand for alternative therapeutic strategies, especially those derived from natural sources. Basil, a common medicinal and culinary herb, contains a range of phytochemicals including flavonoids, essential oils, and phenolic compounds known for their antioxidative and anti-inflammatory properties. This paper affords a complete theoretical evaluation of how basil extract may want to affect the metabolism, organ function, and blood parameters of rats uncovered to prolonged HFD, counting on previous experimental facts and biochemical reasoning to support the assumptions. The findings of this research may manual the layout of destiny experimental and scientific studies targeted on natural interventions for metabolic dysfunction.